Personality and burglary: A virtual reality study. (October 2022) - van Sintemaartensdijk, Iris; van Prooijen, Jan-Willem; Nee, Claire; Otte, Marco; van Lange, Paul
Abstract: Personality traits are robust predictors of the likelihood of involvement in criminal behaviour, but how such traits predict behaviour while committing a crime is unclear. This study investigates associations between HEXACO personality traits and burglars' scouting process, as well as how burglars differ in this respect from non-offenders due to their unique burglary expertise. In a virtual reality experiment, 181 incarcerated burglars and 172 non-offenders (university students) were asked to scout two virtual neighbourhoods for potential targets. For burglars, two main findings were observed: (1) lower honesty-humility was associated with increased perceived neighbourhood deterrence and the perceived likelihood of residents intervening, and (2) higher honesty-humility and self-control, but lower conscientiousness were all associated with taking less time scouting and travelling less distance in the virtual neighbourhood as well as target selection (e.g., selecting corner houses). For non-offenders, only extraversion emerged as a trait associated with increased efficiency in scouting the neighbourhood. We conclude that honesty-humility, conscientiousness, and self-control are primarily associated with the burglar scouting process, and suggest that burglary expertise is key to explaining why these effects were only observed for burglars rather than non-offenders. Highlights: How personality traits predict behaviour while committing a crime is unclear. Burglars and non-burglars scouted neighbourhoods in virtual reality. Honesty-humility, conscientiousness, and self-control are associated with scouting process. Burglary expertise is key to explaining why these effects were only observed for burglars.